Evaluation of Idiopathic Late Onset Nephrotic Syndrome in Children - Dr. P. Ravindranath Reddy; Dr. Grace Aparanji; Dr. D. Nagarjuna, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Idiopathic nephrotic syndrome is defined by the combination of a nephrotic syndrome (proteinuria, hypoalbuminemia, hyperlipidemia, and edema) and non-specific histological abnormalities of the kidney. The prevalence of NS is estimated at 2 to 7 per 100,000 children around the world. Children between 2 to 7 years of age get affected by this condition more often, particularly boys. Materials and Methods: A Retrospective study of hospital records. Case sheets of children admitted in department of pediatrics, Government General Hospital, Kurnool with nephrotic children above the age of 10 years From January 2020 to December 2024. Children aged more than 10 years at onset fulfilled in the diagnostic criteria for nephrotic syndrome were included in the study. Secondary causes of nephrotic syndrome. (eg:SLE, Hepatitis B/C, Diabetic mellitus) were excluded from the study. Clinical data including age at onset, gender, presenting sympotoms and laboratory findings will be recorded histopathlogical finding will be categorized. Treatment response to steroids will be evaluated. Results: The study included 108 children who were followed for a minimum duration of one year. The mean (±sd) age of the population was 13.3 (±1.4) years. The gender distribution of the population was males accounting for 66.7% and females at 33.3%. Hypertension was observed in 8(14.8%). Haematuria in microscopy was found in 28 (51.9%) study participants. Anti-Nuclear Antibodies investigation was done for 50 children and only 3(5.6%) were found to be positive. After the six weeks of steroidal therapy complete remission was found in 58 (53.7%) participants. No remission and partial remission were observed in 26 (24.1%) and 24 (22.2%) members of the study population respectively. Based on the response to steroidal therapy the participants were diagnostically classified as SRNS in 52 (48.1%) children followed SSNS in 50 (46.29%) children. Conclusion: In our study most of the patients were diagnosed with SRNS and SSNS, and most common histological findings were MCNS, MES HC, FSGS and MESPGN. Late onset NS has higher frequency of atypical features, steroid resistance, and histopathology showing lesions other than MCD. Early biopsy may be useful guide to management.